Research progress and state-of-the-art on solar membrane desalination - Maryam Nooman AlMallahi; Jawad Mustafa; Ali H. Al-Marzouqi; Mahmoud Elgendi (Case Studies in Chemical and Environmental Engineering)
The global problem of water scarcity continues to grow because of population growth and climate change. Membrane distillation (MD) stands out as a progressing technology, demonstrating the potential for integration with operating systems powered by solar energy. Despite the increasing interest in solar-powered MD, existing literature primarily focuses on the technical aspects of the technology. There is a notable lack of comprehensive analyses that explore broader research trends, key contributors, and thematic evolution within this field. This paper addresses this gap by employing bibliometric analysis and machine learning approaches to explore trends in solar membrane desalination based on publications from 2014 to 2023. 991 publications were analyzed from various aspects, such as publications, countries, institutions, and research trends. Hot keywords include “membrane distillation”, “reverse osmosis”, “energy efficiency”, and “evaporation”. China had the highest number of publications and h-index, followed by the United States, and Saudi Arabia. The study clustered the keywords into three themes: membrane distillation, membrane materials, and reverse osmosis. Analysis of the thematic map reveals seven main research topics in solar-powered membrane desalination, classified according to their degree of relevance. Finally, future directions of membrane desalination are highlighted, including exploring economic and environmental aspects.